Signatures of adaptation and symbiosis in genomes and transcriptomes of Symbiodinium. Issue 1 (December 2017) - González-Pech, Raúl; Ragan, Mark; Chan, Cheong
Abstract Symbiodinium is best-known as the photosynthetic symbiont of corals, but some clades are symbiotic in other organisms or include free-living forms. Identifying similarities and differences among these clades can help us understand their relationship with corals, and thereby inform on measures to manage coral reefs in a changing environment. Here, using sequences from 24 publicly available transcriptomes and genomes ofSymbiodinium, we assessed 78, 389 gene families inSymbiodinium clades and the immediate outgroupPolarella glacialis, and identified putative overrepresented functions in gene families that (1) distinguishSymbiodinium from other members of Order Suessiales, (2) are shared by all of theSymbiodinium clades for which we have data, and (3) based on available information, are specific to each clade. Our findings indicate that transmembrane transport, mechanisms of response to reactive oxygen species, and protection against UV radiation are functions enriched in allSymbiodinium clades but not inP. glacialis . Enrichment of these functions indicates the capability ofSymbiodinium to establish and maintain symbiosis, and to respond and adapt to its environment. The observed differences in lineage-specific gene families imply extensive genetic divergence among clades. Our results provide a platform for future investigation of lineage- or clade-specific adaptation ofSymbiodinium to their environment.